2016
DOI: 10.1051/0004-6361/201628170
|View full text |Cite
|
Sign up to set email alerts
|

Detection of H3+auroral emission in Jupiter’s 5-micron window

Abstract: We use high-resolution ground-based observations from the VLT CRIRES instrument in November 2012 to identify sixteen previously undetected H + 3 emission lines from Jupiter's ionosphere. These emission lines are located in Jupiter's 5-micron window (4.5−5.2 µm), an optically-thin region of the planet's spectrum where the radiation mostly originates from the deep troposphere. The H + 3 emission lines are so strong that they are visible even against this bright background. We measure the Doppler broadening of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Melin et al () and Tao et al () found that non‐LTE effects increase with altitude, where the temperature is higher and the density is lower. Giles et al () detected H 3 + lines in Jupiter's auroral regions in the 5 μm window and this was the first and only study to date to measure all three temperatures simultaneously. They obtained a kinetic temperature of 1390 ± 160 K, a rotational temperature of 960 ± 40 K, and a vibrational temperature of 925 ± 25 K. These three temperature values are not all in agreement with each other, which indicates a departure from LTE.…”
Section: Discussionmentioning
confidence: 92%
“…Melin et al () and Tao et al () found that non‐LTE effects increase with altitude, where the temperature is higher and the density is lower. Giles et al () detected H 3 + lines in Jupiter's auroral regions in the 5 μm window and this was the first and only study to date to measure all three temperatures simultaneously. They obtained a kinetic temperature of 1390 ± 160 K, a rotational temperature of 960 ± 40 K, and a vibrational temperature of 925 ± 25 K. These three temperature values are not all in agreement with each other, which indicates a departure from LTE.…”
Section: Discussionmentioning
confidence: 92%
“…The Juno mission Bolton et al [2017] and Connerney et al [2017] provides the first occasion to study the South Pole aurora of Jupiter in homogeneous and simultaneous observing conditions. Past analyses [Kim et al, 2009[Kim et al, , 2015Giles et al, 2016], conducted from ground-based observations, have been challenged by using spectra obtained on different dates with different sky conditions. One of the primary objectives of the Juno mission is to clarify the auroral mechanisms at play.…”
Section: Research Lettermentioning
confidence: 99%
“…CRIRES is a cryogenic high-resolution infrared echelle spectrograph [Käufl et al, 2004], which provides long-slit (0.2×40") spectroscopy with a resolving power of 96,000. The CRIRES observations used in this paper have previously been used to study the latitudinal variability in Jupiter's tropospheric disequilibrium species [Giles et al, 2017] and the H 3 + auroral emission [Giles et al, 2016]. In this paper, these CRIRES observations are used to study NH 3 absorption in the 5-µm window.…”
Section: Crires Observationsmentioning
confidence: 99%